The Role of Green Public Procurement in Sustainable Economy Development - Sergacheva, Olga A. (جامعة المنصورة - كلية الحقوق, 2023)
This article is devoted to the study of the sustainable public procurement role in Russia and abroad in preventing climate threats and environmental degradation. It has been proved that the introduction into national legislation of quality standards for purchased goods, works and services that comply with environmental requirements in the future will allow us to come to a sustainable economy system, improve the environmental situation and prevent adverse climate change not only in individual countries, but throughout the world.
Keywords: الاقتصاد المستدام -- الأزمات المناخية -- التشريعات الوطنية